Briket Arang dari Limbah Tempurung Kemiri dan Serbuk Gergajian Kayu Sengon dengan Perekat Arpus (Gum Resin) Menggunakan Proses Karbonisasi - Raffi Abimanyu; Farhan Muhammad Zuhdi; Mutasim Billah; Novel Karaman; Caecilia Pujiastuti (Universitas Islam Raden Rahmat, Malang, 2024)
The type of alternative energy that can be used to replace non-renewable energy is biomass. Researchers will focus on making biomass, namely making charcoal briquettes from candlenut shell waste and wood sawdust, where these two basic materials have very good potential to be used as basic materials for making charcoal briquettes. Each material is carbonized to become charcoal. The carbonized charcoal is uniform in size to 60 mesh. Candlenut shell charcoal and sawdust charcoal are mixed in a ratio of 9:1, 8:2, 7:3, 6:4, 5:5 and arpus adhesive 7, 9, 11, 13, 15 grams. The briquette samples are molded and dried. The research results obtained the highest fixed carbon value from a 9:1 composition with 15gram adhesive of 73.77% and a calorific value of 5375.25 cal/g. These results have met quality standards according to SNI No.1/6235/2000.